2012
DOI: 10.1095/biolreprod.111.092676
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Reproductive Patterns in Przewalski's Mares Are Associated with a Loss in Gene Diversity1

Abstract: The ex situ population of the Przewalski's horse (Equus ferus przewalskii) is not self-sustaining (20% foaling rate), and the demography is skewed toward aging individuals with low gene diversity. We designed the present study to gain a better understanding of the reproductive biology of the Przewalski's mare and to determine whether age and gene diversity influenced reproductive function. Urine samples were collected 3-7 days/wk from 19 mares from May to September, and ultrasound examinations of follicular st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
1
16
2
Order By: Relevance
“…This contrasts with descriptions of the Catalan breed, most of whose ovulations were asynchronous, with intervals ranging from 1 to 9 days [13]. In our study, the maximum interval found between multiple ovulations was 2.48 days, which is longer than that reported for Pêga jennies [9] but resembling that reported for Przewalski's mares [33] or standard jennies [5].…”
Section: Discussioncontrasting
confidence: 99%
“…This contrasts with descriptions of the Catalan breed, most of whose ovulations were asynchronous, with intervals ranging from 1 to 9 days [13]. In our study, the maximum interval found between multiple ovulations was 2.48 days, which is longer than that reported for Pêga jennies [9] but resembling that reported for Przewalski's mares [33] or standard jennies [5].…”
Section: Discussioncontrasting
confidence: 99%
“…An increase in juvenile mortality and decrease in life expectancy throughout successive generations of inbreeding have been reported (Ryder and Wedemeyer, 1982) and in the Przewalski horse it has been shown that animals with inbreeding coefficients of 0.25 or higher originated fewer descendants, possibly because inbreeding may affect ovarian function (Collins et al, 2012), and had a shorter life expectancy than those with lower inbreeding coefficients (Bouman and Bos, 1979). In the Lusitano breed, Oom (1992) showed that animals with higher inbreeding coefficients are more likely to produce non-viable offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Even though most evidence on the effects of inbreeding on fitness components in horses is on juvenile survival, inbred individuals that survive until adulthood may still suffer from inbreeding depression, expressed as lowered survival, growth rate, fertility, inability to mate, reduced fecundity, and insufficient parental care (e.g. Ryan et al, 2003;Charlesworth and Willis, 2009;Collins et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There are seven extant species in the Equidae family [1] and only a few published reproductive studies, including those for the Grévy's zebra (Equus grevyi) [2], mountain zebra (Equus zebra) [3,4], plains zebra (Equus burchellii) [5,6], and Przewalski's horse (Equus ferus przewalski) [7][8][9]. The reproductive physiology of wild asses (three species; eight subspecies [10]) has been largely ignored.…”
Section: Introductionmentioning
confidence: 99%
“…We were interested in determining whether basic knowledge about endocrine patterns and ovarian follicular dynamics in females and seminal traits and sperm sensitivity to cryopreservation in males would provide adequate information to test the efficacy of AI. Our study was novel and possible for this obstinate equid because of our facilities' specialized chutes and restraint devices, our significant reliance on noninvasive monitoring of hormone metabolites [8,9], and our experience collecting semen from other (anesthetized) wild equids [7]. We predict that if indeed AI proves successful in the Persian onager, then the large scale distribution and use of frozen semen across holding institutions could more rapidly help develop a sustainable population to conserve subspecies integrity.…”
Section: Introductionmentioning
confidence: 99%